2018
DOI: 10.1080/14634988.2018.1528816
|View full text |Cite
|
Sign up to set email alerts
|

The Rouge River Area of Concern - A multi-year, multi-level successful approach to restoration of Impaired Beneficial Uses

Abstract: Citizen outcry in the 1960s led to passage of the 1972 U.S. Clean Water Act. Expansion of industrial permitting and availability of federal grants to municipalities controlled industrial waste and untreated municipal sewage entering the Rouge River. However, many sources persisted – notably wet weather discharges, stormwater runoff, and contaminated sediments. This remaining pollution led state officials to cooperatively craft the Rouge River Remedial Action Plan in 1985. This plan addressed all pollution sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For instance, early in the Rouge River RAP, stakeholders learned that to solve their problems of the release of raw sewage from 168 combined sewer overflows and urban stormwater runoff it would take collaboration among all 48 watershed communities and three counties [ 37 ]. The incorporation of the Alliance of Rouge Communities, whose purpose is to “provide an institutional mechanism to encourage watershed-wide cooperation and mutual support to meet water quality permit requirements and to restore beneficial uses of the Rouge River to the area residents”[ 37 ] exemplifies how a watershed focus can be reflected in institutional arrangements. Thus, elevating the watershed perspective is another example of how local organizations have supported and facilitated an ecosystem approach in RAPs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, early in the Rouge River RAP, stakeholders learned that to solve their problems of the release of raw sewage from 168 combined sewer overflows and urban stormwater runoff it would take collaboration among all 48 watershed communities and three counties [ 37 ]. The incorporation of the Alliance of Rouge Communities, whose purpose is to “provide an institutional mechanism to encourage watershed-wide cooperation and mutual support to meet water quality permit requirements and to restore beneficial uses of the Rouge River to the area residents”[ 37 ] exemplifies how a watershed focus can be reflected in institutional arrangements. Thus, elevating the watershed perspective is another example of how local organizations have supported and facilitated an ecosystem approach in RAPs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Tuchman et al, (2018) have shown the importance of public-private partnerships in achieving sediment remediation in AOCs and Hartig et al, (this issue) have demonstrated the importance of partnerships in achieving habitat rehabilitation and restoration in AOCs. French et al, (2018) and Ridgway et al, (2018) both demonstrated the necessity of partnerships to raise necessary funds, achieve local ownership and pride in projects, and build a record of success to help sustain momentum for this restoration work over several decades.…”
Section: Lesson 7: Pursue Creative Financingmentioning
confidence: 99%